The Application of Microsoft Teams in Efforts to Improve Sociolinguistic Learning for Third Semester Students of PBSI at Al Washliyah Muslim University of Nusantara - Abdullah Hasibuan; Nirmawan Nirmawan; Nurima Rizki Dongoran (Westscience Press, 2025)
This study evaluates the implementation of Microsoft Teams as a learning medium to improve the understanding of sociolinguistic concepts among Semester III A students of the Indonesian Language and Literature Education (PBSI) Study Program at Al Washliyah Muslim Nusantara University (UMN). The main focus of the study is to see the effectiveness of the Microsoft Teams platform in increasing participation, communicative interaction, and understanding of sociolinguistic content. The research method uses a quantitative and qualitative approach with a pretest–posttest design. The results of the study indicate an increase in student learning performance in the aspects of discussion participation, interactive engagement, and understanding of sociolinguistic material after the use of Microsoft Teams as a learning medium with a good category with an average score of 81.9. The results of the paired sample t-test showed that there was a significant difference between the pretest and posttest results of students' sociolinguistic understanding after the implementation of Microsoft Teams-based learning (t = 198.07; p < 0.05). These findings indicate that the integration of digital collaborative applications can effectively support social context-based language learning.